Hybrids and synthetic varieties of blue corn for Central Highlands of Mexico: agronomic potential and yield stability - Arellano Vázquez José Luis; Rojas Martínez Israel; Gutiérrez Hernández Germán Fernando (Revista Mexicana de Ciencias Agrícolas, 2018)
The objectives of this study were 1) to determine the agronomic potential of hybrid and synthetic varieties of blue corn through the silking period, lodging resistance, production of cobs per plant and yield; and 2) to determine yield stability of hybrids and synthetic varieties and select stable genotypes and best response to environments of rainfed limited and rainfed with irrigation. 14 trilinear hybrids were evaluated, 10 synthetic varieties and a landrace from the region. The experimental design was randomized complete block with three replications. The experiment was established in the state of Tlaxcala, in the localities of Benito Juárez and Tlacualpan under rainfed conditions and in Huamantla and Calpulalpan under rainfed with two irrigations. The combined analysis of variance detected differences (p≤ 0.001) between localities and hybrids for days to silking, lodging, cobs per plant and yield in genotype x environment interaction for yield. Among localities yield varied from 7.8 to 10.6 t ha-1, and among hybrids from 7.2 to 10.2. The analysis of genotype x environment interaction allowed to detect the hybrid HA-911 as a stable cultivar with yields of 10.4 t ha-1, for hybrids HA-912 and HA-913 as cultivars that interacted with the best irrigated environment and showed yields of 12.2 and 11.8 t ha-1, respectively, and synthetic varieties VSA-902 and VSA -904 as varieties that interacted with localities of limited rainfed and had limited yields of 9.5 and 9.4 t ha-1, respectively.